Bioremediation for coal-fired power stations using macroalgae. (15th April 2015) - Roberts, David A.; Paul, Nicholas A.; Bird, Michael I.; de Nys, Rocky
Abstract: Macroalgae are a productive resource that can be cultured in metal-contaminated waste water for bioremediation but there have been no demonstrations of this biotechnology integrated with industry. Coal-fired power production is a water-limited industry that requires novel approaches to waste water treatment and recycling. In this study, a freshwater macroalga (genus Oedogonium ) was cultivated in contaminated ash water amended with flue gas (containing 20% CO2 ) at an Australian coal-fired power station. The continuous process of macroalgal growth and intracellular metal sequestration reduced the concentrations of all metals in the treated ash water. Predictive modelling shows that the power station could feasibly achieve zero discharge of most regulated metals (Al, As, Cd, Cr, Cu, Ni, and Zn) in waste water by using the ash water dam for bioremediation with algal cultivation ponds rather than storage of ash water. Slow pyrolysis of the cultivated algae immobilised the accumulated metals in a recalcitrant C-rich biochar. While the algal biochar had higher total metal concentrations than the algae feedstock, the biochar had very low concentrations of leachable metals and therefore has potential for use as an ameliorant for low-fertility soils. This study demonstrates a bioremediation technology at a large scale for a water-limited industry that could be implemented at new or existing power stations, or during the decommissioning of older power stations. Highlights: A water bioremediation technology is demonstrated in situ at a coal power station. Macroalgae was grown in ponds with water from ash disposal and CO2 from flue gas. The macroalgae sequestered metals from the effluent in an efficient process. The cultivated biomass was converted to biochar for value-added applications. Live macroalgae can treat industrial waste water while producing valuable biomass.